Orthorexia nervosa: can healthy eating food trends impact food companies marketing strategies? - Duarte, Paulo (2019)
The purpose of this article is to explore foods companies’ knowledge of food trends and assess how orthorexia nervosa may affect food companies’ marketing decisions. Data was gathered through a multiple case-study approach, and four semi-structured interviews to CEOs/CMOs of food companies from four distinct non-competing sectors of the food industry. The results show that although marketing managers are conscious of the existence of consumer behavior changes regarding food habits, they are not particularly concerned neither interested in micro-segments as they are not profitable. Despite the deficiencies on CMOs’ knowledge of particular food trends they declare to be attentive to the changes in consumer behavior and prepared to respond to competitors moves. This research adds to the existing knowledge on the food industry since it is the first study to explore the impact of food trends on food companies’ management marketing decisions from the company point of view.